2007
DOI: 10.1091/mbc.e07-03-0295
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Common Subnuclear Localization Signal

Abstract: Proteins share peptidic sequences, such as a nuclear localization signal (NLS), which guide them to particular membranebound compartments. Similarities have also been observed within different classes of signals that target proteins to membrane-less subnuclear compartments. Common localization signals affect spatial and temporal subcellular organization and are thought to allow the coordinated response of different molecular networks to a given signaling cue. Here we identify a higher-order and predictive code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 61 publications
(126 reference statements)
2
55
0
Order By: Relevance
“…The localization or exclusion of proteins from the nucleolus is subject to dramatic changes upon cellular stimuli, stress and complete reorganization during cell cycle progression. [23][24][25] In a previous study, we have shown that a reporter protein traverses nucleoli rapidly with less obstruction compared to nucleoplasmic regions rich in chromatin. 26 In that study, we described a structural feature of the nucleolus with channel like regions void of nucleic acids and proteins that facilitates a fast movement of non-nucleolar proteins through this compartment.…”
Section: -11mentioning
confidence: 99%
“…The localization or exclusion of proteins from the nucleolus is subject to dramatic changes upon cellular stimuli, stress and complete reorganization during cell cycle progression. [23][24][25] In a previous study, we have shown that a reporter protein traverses nucleoli rapidly with less obstruction compared to nucleoplasmic regions rich in chromatin. 26 In that study, we described a structural feature of the nucleolus with channel like regions void of nucleic acids and proteins that facilitates a fast movement of non-nucleolar proteins through this compartment.…”
Section: -11mentioning
confidence: 99%
“…The plurifunctional nature of the nucleolus is evident in its response to physiological stimuli and stress conditions accompanied by nucleolar remodeling, and a decrease or interruption in rRNA synthesis [20,21] as well as the capture of numerous seemingly unrelated factors involved in a wide array of cellular functions [22][23][24][25].…”
Section: Long-term Regulationmentioning
confidence: 99%
“…Hallmarks of nucleolar remodeling include a decrease or interruption in rRNA synthesis 8,9 as well as the capture of numerous seemingly unrelated factors involved in a wide array of cellular functions. [10][11][12][13] Though these phenomena have been observed for many years, they have only recently been mechanistically linked to the expression of novel species of noncoding RNA (ncRNA) originating from the ribosomal intergenic spacer (IGS). 13,14 In this Commentary, recent and unexpected advances in our understanding of the transcriptional activity and biological role of the IGS are discussed.…”
Section: Igs Transcript-mediated Regulation Of Rrna Synthesismentioning
confidence: 99%
“…13,40 These proteins share a consensus amino acid sequence that targets them to the IGS for static detention in the nucleolus, the nucleolar detention signal (NoDS). 12,13 This discrete code is composed of an arginine motif (R-R-I/L-X 3 -r) along with several hydrophobic repeats (L-Φ/N-L/V; where Φ represents any hydrophobic residue). 12 Bioinformatic studies suggest that up to 9% of all proteins encode an NoDS and consequently could be regulated by the nucleolus.…”
Section: The Ribosomal Intergenic Spacermentioning
confidence: 99%
See 1 more Smart Citation